Perancangan User Experience Aplikasi Computer Assisted Test (CAT) berbasis Website menggunakan Metode Goal-Directed Design pada Badan Kepegawaian Daerah Kabupaten Lumajang - Riekko Rahmat Rahardian; Retno Indah Rokhmawati; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Regional Personnel Agency (BKD) of Lumajang has the task of carrying out examinations on Civil Servants such as competency exams and requesting test applications called Web-based Computer Assisted Assistance Test (CAT) with displays that can be used for the current examination process. CAT BKD that is suitable for the user's purpose using the Goal-Directed Design method. In implementing the Goal-Directed Design method there are 6 stages, the first stage is research to get the needs of the application from stakeholders and 6 users. Stage modeling that produces persona which contains 6 variables from CAT application users, namely examinees and exam committee. Stages of the requirement definition that produce CAT applications and information structures from the CAT application. Stages design framework that produces the results of designing a CAT application using wireframe. Stage design improvements that produce a hi-fi prototype. And the support design stages that produce the analysis of the results of the prototype testing qualitatively are user testing and quantitative, namely the experience of the user questionnaire (UEQ). The results of UEQ on the exam participants' interface yielded very good categories on the scale of attraction, efficiency, stimulation, and novelty and gained categories both on the scale of perspicuity and dependability. While the appearance of the exam committee produced a excellent category on the sixth scale of UEQ. From these results it can be concluded that the CAT BKD application is good for the examinee and the exam committee providing a perception that is good for the user.